Wind-induced seismic noise at the Princess Elisabeth Antarctica Station - Frankinet, Baptiste; Lecocq, Thomas; Camelbeeck, Thierry (2021)
Icequakes are the result of processes occurring within the ice mass or between the ice and its environment. Studying icequakes provides a unique view on ice dynamics, specifically on the basal conditions. Changes in conditions due to environmental or climate changes are reflected in icequakes. Counting and characterizing icequakes is thus essential to monitor them. Most of the icequakes recorded by the seismic station at the Belgian Princess Elisabeth Antarctica Station (PE) have small amplitudes corresponding to maximal displacements of a few nanometres. Their detection threshold is highly variable because of the rapid and strong changes in the local seismic noise level. Therefore, we evaluated the influence of katabatic winds on the noise measured by the well-protected PE surface seismometer. Our purpose is to identify whether the lack of icequake detection during some periods could be associated with variations in the processes generating them or simply with a stronger seismic noise linked to stronger wind conditions. We observed that the wind mainly influences seismic noise at frequencies greater than 1ĝ€¯Hz. The seismic noise power exhibits a bilinear correlation with the wind velocity, with two different slopes at a wind velocity lower and greater than 6ĝ€¯mĝ€¯s-1 and with, for example at a period of 0.26ĝ€¯s, a respective variation of 0.4ĝ€¯dBĝ€¯(mĝ€¯-1ĝ€¯s) and 1.4ĝ€¯dBĝ€¯(mĝ€¯-1ĝ€¯s). These results allowed a synthetic frequency and wind-speed-dependent noise model to be presented that explains the behaviour of the wind-induced seismic noise at PE, which shows that seismic noise amplitude increases exponentially with increasing wind speed. This model enables us to study the influence of the wind on the original seismic dataset, which improves the observation of cryoseismic activity near the PE station. SCOPUS: ar.j info:eu-repo/semantics/published